Height-based equations as screening tools for elevated blood pressure in the SAYCARE study , Journal of Clinical Hypertension (2020)
ABSTRACT: This study evaluated the accuracy of four height-based equations: blood pressure to height ratio (BPHR), modified BPHR (MBPHR), new modified BPHR (NMBPHR), and height-based equations (HBE) for screening elevated BP in children and adolescents in the SAYCARE study. We measured height and BP of 829 children and adolescents from seven South American cities. Receiving operating curves were used to assess formula performance to diagnose elevated BP in comparison to the 2017 clinical guideline. Sensitivity, specificity, and positive and negative predictive values (PPV, NPV) were calculated for the four screening formulas. The diagnostic agreement was evaluated with the kappa coefficient. The HBE equation showed the maximum sensitivity (100%) in children, both for boys and girls, and showed the best performance results, with a very high NPV (>99%) and high PPV (>60%) except for female children (53.8%). In adolescents, the highest sensitivity (100%) was achieved with the NMBPHR for both sexes. Kappa coefficients indicated that HBE had the highest agreement with the gold standard diagnostic method (between 0.70 and 0.75), except for female children (0.57). Simplified methods are friendlier than the percentile gold standard tables. The HBE equation showed better performance than the other formulas in this Latin American pediatric population.